a=11
To solve:
a/7 - 5/7 = 6/7
Add 5/7 to both sides to get the term with "a" by itself. 5/7 is being added as opposed to subtracted because it is negative. Because of their common denominators, you can just calculate (6+5)/7
a/7 = 11/7
Multiply both sides by 7 since a/7 and 11/7 have this as a common denominator.
a = 11
Good luck :)
2006-10-01 04:22:28
·
answer #1
·
answered by Bob 3
·
0⤊
0⤋
To figure out what a is, add 5/7 to each side giving you a/7=6/7 + 5/7, which gives you a/7=11/7. Now take 11/7 - 5/7 and that gives you 6/7. So your answer is a = 11
2006-10-01 12:21:48
·
answer #2
·
answered by Nick H 1
·
0⤊
0⤋
Well what I'd do first is clear the fractions. Here's how:
a/7 - 5/7 = 6/7
7(a/7) - 7(5/7) = 7(6/7)
now combine like terms:
a - 5 = 7
a = 7 + 5
a = 12
a is 12 whether you've cleared the fractions or not, but you have made your numbers a lot easier to work with!
If all your fractions had not been something over 7, you'd have had to find something in common, like this:
if your problem had been:
a/9 - 5/3 = 6/27
you'd multiply each number by 27 and then simplify:
27(a/9) - 27(5/3) = 27(6/27)
3a - 9(5) = 1(6)
now you should be able to solve any problem like this!
Good luck!
2006-10-01 11:30:36
·
answer #3
·
answered by ronw 4
·
0⤊
0⤋
A/7-5/7=6/7
A-5=6
A=6+5
A=11
2006-10-01 11:25:22
·
answer #4
·
answered by ayeshaashraf4u 2
·
0⤊
0⤋
There is a common denominator of 7, so just forget it a while and use x-5=6; x=6+5; x=11. Then we put it back in and have 11/7-5/7=6/7.
2006-10-01 11:17:42
·
answer #5
·
answered by miyuki & kyojin 7
·
0⤊
0⤋
a/7 - 5/7 = 6/7
a/7 - 5/7 + 5/7 = 6/7 + 5/7
a/7 = 6/7 + 5/7
a/7 = 6 + 5/7
a/7 = 11/7
This can now be solved by proportion
Cross multiply the means and the extremes
7a = 11 x 7
7a = 77
7a/7 = 77/7
Dividing both sides by 7
a = 11
The answer is a = 11
The solution set is { 11 }
Insert the a value into the equation
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Check
a/7 - 5/7 = 6/7
11/7 - 5/7 = 6/7
11 - 5/7 = 6/7
6/7 = 6/7
2006-10-01 12:32:56
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
0⤋
Since you have a common denominator of 7, you can group together the numerators. So that would equal:
(a-5)/7 = 6/7 . Now multiply both sides by 7 and the denominators will cancel out.
(a-5)/7 *7 = 6/7*7
a-5 = 6.
Now solve.
2006-10-01 11:13:38
·
answer #7
·
answered by Manan T 3
·
1⤊
0⤋
since all the denominators are the same (7), the equation simply becomes a-5 = 6. by adding a 5 to each side, you get: a-5+5 = 6+5 => a = 11
There you go, a = 11.
2006-10-01 11:23:51
·
answer #8
·
answered by hooman m 2
·
0⤊
0⤋
all terms are divided by 7 so the 7's cancel out giving:
a - 5 = 6
so a = 6 +5
a = 11
2006-10-01 11:13:04
·
answer #9
·
answered by benabean87 2
·
0⤊
0⤋
Multiply each side by 7, to get a - 5 = 6, in this case, a = 11, so... a = 11!
(No, the exclamation mark is just an exclamation mark.)
2006-10-01 11:18:45
·
answer #10
·
answered by Anonymous
·
1⤊
0⤋